2019
DOI: 10.3390/catal9090779
|View full text |Cite
|
Sign up to set email alerts
|

Selective CO Hydrogenation Over Bimetallic Co-Fe Catalysts for the Production of Light Paraffin Hydrocarbons (C2–C4): Effect of Space Velocity, Reaction Pressure and Temperature

Abstract: Synthetic natural gas (SNG) using syngas from coal and biomass has attracted much attention as a potential substitute for fossil fuels because of environmental advantages. However, heating value of SNG is below the standard heating value for power generation (especially in South Korea and Japan). In this study, bimetallic Co-Fe catalyst was developed for the production of light paraffin hydrocarbons (C2–C4 as well as CH4) for usage as mixing gases to improve the heating value of SNG. The catalytic performance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 24 publications
0
19
0
Order By: Relevance
“…The optimum FTS conditions to produce the highest C2-C4 paraffin products were determined to be H2/CO = 3.0 and 300 °C of reaction temperature at 10 bar for the bimetallic Co-Fe catalyst supported on the γ-alumina, as shown in Figure 18. From additional discussion by Jo et al [105], it was found that CO conversion increases with a decrease in space velocity and with an increase in reaction pressure and temperature, as shown in Figure 19. With increasing reaction temperature, the CH4 yield increases and C2+ yield decreases.…”
Section: Paraffin Productionmentioning
confidence: 84%
See 2 more Smart Citations
“…The optimum FTS conditions to produce the highest C2-C4 paraffin products were determined to be H2/CO = 3.0 and 300 °C of reaction temperature at 10 bar for the bimetallic Co-Fe catalyst supported on the γ-alumina, as shown in Figure 18. From additional discussion by Jo et al [105], it was found that CO conversion increases with a decrease in space velocity and with an increase in reaction pressure and temperature, as shown in Figure 19. With increasing reaction temperature, the CH4 yield increases and C2+ yield decreases.…”
Section: Paraffin Productionmentioning
confidence: 84%
“…Jo et al expeditiously optimized the catalyst design and the operating conditions based on various experimental data, focusing on C 2 -C 4 selectivity and paraffin ratios [104,105]. They investigated the catalytic performances using the various bimetallic (Co and Fe) catalysts on Al 2 O 3 , where the content of Co was varied; their results are shown in Figure 16.…”
Section: Paraffin Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the mutual roles of two reducible transition metal oxides such as the mesoporous Co and Fe oxide nanoparticles for FTS reaction have not been well investigated till now as far as we know with respect to their structural and catalytic stability with its larger amounts of light hydrocarbons without using any acidic zeolites. The highly ordered mesoporous CoÀ Fe mixed bimetal oxide at an optimal Fe/Co molar ratio, which was tested at the similar reaction conditions of the typical FTS reaction, [30] revealed a higher structural stability and olefin selectivity in the C 2 À C 4 hydrocarbons and clean fuels by the synergy effects of active metallic Co and iron carbides. The synergistic effects of those reducible transition metal oxides such as the Co 3…”
Section: Introductionmentioning
confidence: 99%
“…One of them is cobalt and its alloys. These materials have also been used or analyzed during research as a catalytic material [60][61][62][63][64][65].…”
Section: Introductionmentioning
confidence: 99%